Numerical simulation of water hammer in multi-level intake hydropower station considering the impact of intake. Issue 3 (13th March 2019) - Ding, Yuan; Li, TongChun; Zhao, LanHao; Zhou, MinZhe; Lin, ChaoNing
Abstract : Purpose: Multi-level intake structures are used to take the surface water of reservoirs. The changed boundary conditions will certainly make the water hammer phenomenon more complicated. This paper aims to find out the influence and law of the water hammer pressure after setting the stop log gates. Design/methodology/approach: The authors use the computational fluid dynamics method with the adaptive grid technology to stimulate the water hammer phenomenon of the multi-level intake hydropower station. In the analysis, we set several different heights of stop log gates and two representative times in the starting up and shutdown processes to reflect the impact of multi-level intake structures. Findings: The authors find that the setting of the stop log gates will reduce the pressure during the normal operation and will increase the period and amplitude of the water hammer wave, but will not necessarily increase the maximum water hammer pressure during the shutdown process. The relationship between the height of the stop log gates and the amplitude of the water hammer wave is affected by the shutdown time. After setting stop log gates, the depression depth and wave height of the water level in front of the dam increase when the load changes. Originality/value: The authors study in this paper the water pressure of the multi-level intake hydropower station that has never been studied before and obtain some laws.